Neuroimaging Patterns and Function in Cerebral Palsy—Application of an MRI Classification - Himmelmann, Kate; Horber, Veronka; Sellier, Elodie; De la Cruz, Javier; Papavasiliou, Antigone; Krägeloh-Mann, Ingeborg; , The Surveillance of Cerebral Palsy in Europe (SCPE) Collaboration (Frontiers in Neurology, 2021)
Background Cerebral palsy (CP) is a disorder of movement and posture and every child with CP has a unique composition of neurological symptoms, motor severity and associated impairments, constituting the functional profile. Although not part of the CP definition, Magnetic Resonance Imaging (MRI) sheds light on the localisation, nature and severity of brain compromise. The MRI classification system (MRICS), developed by the Surveillance of Cerebral Palsy in Europe (SCPE), describes typical MRI patterns associated with specific timing of vulnerability in different areas of the brain. The classification has proven to be reliable and easy to use. Aims The aim of this study is to apply the MRICS on a large dataset and describe the functional profile associated with the different MRI patterns of the MRICS. Material and methods Data on children with CP born in 1999-2009 with a post-neonatal MRI from 20 European registers in the JRC-SCPE Central Registry, was included. The CP classification and the MRICS was applied, The Gross Motor Function Classification (GMFCS) and the Bimanual Fine Motor Function (BFMF) classification were used. The following associated impairments were documented: intellectual impairment, active epilepsy, visual impairment, and hearing impairment. An Impairment index was used to characterize severity of impairment load. Results The study included 3818 children with postneonatal MRI. Distribution of CP type, motor and associated impairments differed by neuroimaging patterns. Functional profiles associated with neuroimaging patterns were described, and the Impairment index showed that bilateral findings were associated with a more severe outcome both regarding motor impairment and associated impairments than unilateral compromise. The results from this study, particularly the differences in functional severity regarding uni-and bilateral brain compromise, may support counselling and service planning of support of children with CP.